A Chromosomal-level genome assembly and annotation of fat greenling (Hexagrammos otakii) - Li Li; Fawen Hu; Dong Liu; Xiaolong Wang; Jing Diao; Yijing Zhu; Fengxiang Gao; Ying Fan; Yuxia Jian; Xue Wang; Lei Pan; Wen Guo (Scientific Data)
Abstract Fat greenling (Hexagrammos otakii Jordan & Starks, 1895) is a valuable marine fish species, crucial for aquaculture in Northern China due to its high-quality meat and significant economic value. However, the aquaculture industry faces challenges such as trait degradation, early sexual maturity, and disease susceptibility, necessitating advanced genomic interventions for sustainable cultivation. This study presents the first chromosomal-level genome assembly of H. otakii, achieved using PacBio long-read sequencing and Hi-C technology. The assembly yielded a genome size of 682.43 Mb with a contig N50 size of 2.39 Mb and a scaffold N50 size of 27.83 Mb. The completeness of genome assessed by BUSCO is 96.99%. A total of 22,334 protein-coding genes were predicted, with 21,619 (96.80%) functionally annotated across various protein databases. This genomic resource is a step forward in supporting the breeding, germplasm conservation, and enhancement of H. otakii, facilitating genetic studies and the development of strategies for disease resistance and growth optimization in aquaculture.